Aconselhamento pastoral com pessoas em situação de depressão: um estudo teórico na perspectiva da prática do cuidado - Matias, Fernando José (2014)
Depression is one of the most frequent disorders, conditions and states within contemporary humanity, so much so that it has been called the psychopathology cold . We live in times of depressions. This prevalence has caused it to impose itself as one of the most challenging situations in current society, thus revealing the need for alternatives which are methodologically reflected upon and deepened in the various areas of knowledge, especially the Human Sciences. In the area of theology, we have opted to focus this present work on pastoral counseling. This because it has its main concerns and interactions related to human suffering, be it individual or collective. In this sense pastoral counseling, which has as a base the Christian faith and the ecclesial community as a therapeutic space of care, presents precious tools, which, as a practical and methodologically reflected action, aim at also interacting, understanding and intervening in what goes on with the person suffering with depression. Therefore, the present research analyzes how pastoral care and pastoral counseling can be developed as ways of caring for people in situations of depression. For this, it verifies the main implications, influences and characteristics of depressions and the states of depression in human life and it does this especially through contributions from the areas of psychiatry and psychology, thus establishing an interdisciplinary dialog of both of these with theology in the construction and improving that which involves the task of knowing how to care for someone. This present thesis is especially tied to the area of Practical Theology, more specifically to caring, pastoral care and pastoral counseling of people weakened by various forms of depression, be they visible or invisible, maintaining itself firm in seeking the promotion of a dignified, transformed and liberated life.